Characterization of the coal derived humic acids from Mukah, Sarawak as soil conditioner - Sim Siong, Fong; Lau, Seng; Wong Nan, Chong; Janice, Asing; Muhammad Faizal, Md Nor; Amira Satirawaty, Mohd PauzanI (Sociedade Brasileira de Química, 2006)
In Malaysia, abundant coal resources were found in Sarawak and Sabah. The utilization of coal resources, to date, is emphasized on the energy productions. The non-energy utilization as soil conditioner is unexplored. Therefore, this study attempted to characterize the coal humic acids extracted from Mukah coal and to evaluate its properties as soil conditioner. The coal humic acids from the regenerated sample were also assessed. The results revealed that different extractants and concentrations influenced the properties of humic acids. The extraction with KOH at 0.5 mol L-1 produced humic acids with low ash content and high acidic functional groups, which are substantial as soil conditioner. However, the yield was low. Regeneration of coal sample with 10% nitric acids improved the yield to an average of 83.45%. The acidic functional groups of nitrohumic acids were improved with the ash content remained at a low level.